'It's not the fact they claim benefits but their useless, lazy, drug taking lifestyles we despise': Analysing audience responses to Benefits Street using live tweets. (March 2018) - van der Bom, Isabelle; Paterson, Laura L.; Peplow, David; Grainger, Karen
Highlights: Tweets as live audience responses to the TV programme Benefits Street II. Corpus of data comprises 11, 623 tweets sourced from over 4000 Twitter accounts. Our analysis examines public reactions to mediatised constructions of poverty. Tweeters draw upon scrounger, underclass, and flawed consumerism discourses. Benefits claimants are typified as non-human 'creatures' and objectionable beings. Abstract: This paper capitalises on the instantaneity of Twitter as a communicative medium by analysing live audience responses to the second series of the controversial television programme Benefits Street. We examine the discourses and representation of social class drawn upon in public reactions to the program. We compiled a corpus of live tweets that were sent during the first airing of each episode of Benefits Street II, which included the hashtags #BenefitsStreet and/or #BenefitStreet. Our corpus comprises 11, 623 tweets sourced from over four thousand Twitter accounts. Drawing on techniques from corpus-based discourse analysis, and contrasting our findings to an earlier study on Benefits Street by Baker and McEnery (2015a), we offer an insight into viewers' discursive constructions of benefit claimants not just as scroungers, but as a more generally morally inadequate and flawed underclass. We argue that poverty porn programmes such as Benefits Street encourage viewers to see any positive representations of benefits claimants as exceptions to the rule.